A Multiple Regression Model On The Relationship Between Deliberative Democracy And Political Equity: The Cases Of Greece And Turkey - Anthony Papaoikonomou (İmgelem)
This article presents a multiple regression model in which the effect of the political equality index on the quality of deliberative democracy in Greece and Turkey is investigated. The data was drawn from the V-Dem (Varieties of Democracy) database which was announced in March 2024. As far as Greece is concerned, the final conclusions of the research include the positive effect of increasing the participation of women and LGBTI people on the index of deliberative democracy. Also, an interesting finding is the fact of the absence of importance of the participation of individuals in primary and secondary education in deliberative democracy, a fact that may be linked to the discredit of the Greek school. As far as Turkey in concerned, there is a negative relationship between the participation of citizens in tertiary education, as well as a negative relationship between the distribution of power by sexual orientation and deliberative democracy index. Finally, the participation of citizens in primary education has a positive coefficient and is highly statistically significant.